(untitled) (International Journal of Business Innovation, 2023)
Nepal was restructured in 2015 and formed seven provinces according to the new constitution. Out of them, Madhesh province is located in the mid-southeast part of Nepal consisting of 136 local governments in 8 districts. Clause 21(4) of the Intergovernmental Fiscal Arrangement Act (2017) states that local government has to be capable of covering the administrative cost with internal revenues and the revenue shared by the central and provincial governments. Present laws and policies of the Nepal government have delegated exclusive power to the local governments. Section 5(1) of the Federation, Province, and Local Level (Coordination and Inter-relation) Act (2020) has provisioned power to the federal, provincial, and local governments to enact necessary laws, policies, and plans on the matters of respective powers delegated by the constitution and implement such powers for the local development. Based on this, local government has to formulate laws and frame development plans. This research has been carried out to understand what municipalities have done and what can be the way forward for strengthening the local economy. To study the aimed objective, mixed methods have been applied. Evidence revealed that the percentage of unregistered businesses is 68. The percentage of the LED budget is 5, actual expenditure is 3, and priority is 4. Out of the LED budget, emphasis on the agriculture sector is high since municipalities have allocated 68% of the total LED budget to this sector. Municipalities are suggested to establish regular progress reviews because the achievements measurement system is lacking.